2009
DOI: 10.1016/j.ejcts.2009.02.017
|View full text |Cite
|
Sign up to set email alerts
|

What the cardiac surgeon needs to know prior to aortic valve surgery: impact of echocardiography

Abstract: Echocardiographic assessment prior to valve surgery is crucial for clinical decision making, timing of surgery, planning the adequate surgical therapy and predicting the patient's outcome. Description of transvalvular velocities is not enough for sending a patient to the operating room. There are specific functional and morphological characteristics of each valve dysfunction that have to be addressed by the echocardiographer prior to surgery. Evaluation of the aortic valve, annulus, root, ascending aorta, left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Pre- [11] and intraoperative [12] echocardiography of the heart is an indispensible examination for patients undergoing cardiac valve surgery. Whereas transthoracal echocardiography is less invasive and more convenient to the patient, several studies have demonstrated transesophageal echocardiography to be superior for assessing possible sources of cardiac embolism [13], such as intracardiac thrombi or intramural lesions [14].…”
Section: Discussionmentioning
confidence: 99%
“…Pre- [11] and intraoperative [12] echocardiography of the heart is an indispensible examination for patients undergoing cardiac valve surgery. Whereas transthoracal echocardiography is less invasive and more convenient to the patient, several studies have demonstrated transesophageal echocardiography to be superior for assessing possible sources of cardiac embolism [13], such as intracardiac thrombi or intramural lesions [14].…”
Section: Discussionmentioning
confidence: 99%